Exploring the hypothesis of differential care for African immigrant and native women in France with hypertensive disorders during pregnancy: a qualitative study. (15th May 2017) - Sauvegrain, P; Azria, E; Chiesa‐Dubruille, C; Deneux‐Tharaux, C
Abstract : Objective: To analyse whether prenatal care trajectories among women with hypertensive disorders during pregnancy in France differ between immigrants from sub‐Saharan Africa (SSA) and native French women. Design: Qualitative interview study. Setting: Three public maternity units in the Paris region. Population: Women born in SSA or in France of French parents and treated for hypertension or pre‐eclampsia during their pregnancy. Methods: A sociologist conducted semi‐structured in‐depth interviews of 33 women during their postpartum hospitalisation and collected data from their medical files. n 'vivo 10 (QSR International) was used for line‐by‐line coding of the transcriptions, to identify emerging themes. Strauss's concept of illness trajectories was then applied to these data. Main outcome measures: Themes derived from interviews. Results: Women reported during the interviews that the blood pressure measurement procedures used by hospital staff varied between the two groups, and their medical records supported this finding. Repeated urinary dipstick testing of proteinuria before laboratory testing was more frequent for African women, as was the failure to further test proteinuria levels requiring additional action. The two groups received similar standardised care after severe complications. Other findings showed that African women were less likely to rely on healthcare services. Conclusions: These results suggest non‐medically justified differential prenatal care between African and native women that may have helped delay the diagnosis of hypertension or pre‐eclampsia. This study suggests hypotheses for further quantitative studies to explore the potential involvement of this differential care in the higher frequency of severe complications in this subgroup, concordantly reported in European countries hosting SSA migrants. Tweetable abstract: Differential prenatal care may delay diagnosis of pre‐eclampsia among African compared with native French women. Tweetable abstract: Differential prenatal care may delay diagnosis of pre‐eclampsia among African compared with native French women.